Muscular metastasis from gastric cancer - Lourenço, Laércio Gomes; Carlotto, Jorge Roberto Marcante; Herbella, Fernando Augusto Mardiros; Silva, Diego Adão Fanti; Setti, Henrique Barroso (Journal of Gastrointestinal Oncology; Vol 5, No 6 (December 20, 2014): Journal of Gastrointestinal Oncology, 2014)
The association between gastric cancer and muscle metastasis is extremely rare. Few cases have been reported in the literature. We report a case of a 68-year-old man, with a diagnosis of gastric adenocarcinoma by endoscopy and biopsy. A painful nodule on the right thigh became noticeable during chemotherapy sessions, where positron emission tomography and percutaneous biopsy diagnosed a muscle metastasis of gastric adenocarcinoma. This report demonstrates the importance of further investigation of muscle lesion in patients with gastrointestinal cancer and how we can diagnose and treat these lesions.